Exploring women’s thoughts on self-weighing during pregnancy: results of the Self-Weighing in Pregnancy: Experiences (SWIPE) study - Anne E. Ferrey; Nerys M. Astbury; Yvonne Kenworthy; Lucy Mackillop; Kerstin Frie; Susan A. Jebb (BMC Pregnancy and Childbirth, 2021)
Abstract Background Excess gestational weight gain is common and an important risk factor for adverse pregnancy outcomes. Regular weighing can be used to assess and manage weight gain, but NICE guidelines do not recommend routine weighing during antenatal care. Trials that have tested the effectiveness of self-weighing to manage GWG have been unsuccesful in engaging women in regular self-weighing, although the reasons for lack of engagement are not fully understood. This study aimed to understand why this lack of engagement occurred by exploring the naturally occurring thoughts and feelings of pregnant women (9 to 15 weeks gestational age) who were asked to weigh themselves at home. Methods Twenty-five women were recruited to take part. Participants completed short questionnaires at their first-trimester and 20-week scans. After recruitment, participants were asked to weigh themselves at roughly the same time each week for 8 weeks. Whilst they weighed themselves they were asked to audio-record their current weight and describe any thoughts or feelings that occurred as they weighed themselves. These audio recordings were then sent to researchers using a secure messaging service. Results Most of the recruited women (56%) were unaware of guidelines for gestational weight gain, and only 40% could identify the ideal rate of GWG for their BMI group. Thematic analysis of the think-aloud recordings resulted in three main themes: “understanding weight gain in pregnancy”, “taking action to prevent weight gain” and “reactions to self-weighing”. Overall, there was a relatively positive response to self-weighing and some participants used self-weighing to reflect on the reasons for weight gain and plan actions they could take to avoid excess gain. Negative emotional responses tended to be related to a lack of guidance about what level of weight gain or loss was “healthy”, or to other worries about the pregnancy. Of the women recruited who submitted at least one think aloud recording (n 10), 80% found self-weighing to be useful, and said they would likely continue to self-weigh at home. Conclusions Women had complex emotions about self-weighing during pregnancy but overall found it useful, suggesting it could be encouraged as part of self-regulatory interventions to control GWG. Clear guidelines about appropriate gestational weight gain could help to reduce anxiety. Trial registration The study was prospectively registered with ISRCTN ISRCTN10035244 .